Pour une théorie des idéologies en anthropologie - Gendreau, Andrée (Anthropologica, 2022)
Since Marx, the function of ideology as an object of sociological knowledge has raised a number of questions. The present paper first attempts to survey the main contemporary theories of ideology and then goes on to assess the role assigned to the analysis of ideologies within various anthropological trends. A theory that prove to be operational in a fieldwork context (Auge, Veron) is finally suggested: ideology would be a logic, a system of interpretation and production of meaning.